Human-based evidence for the therapeutic potential of arginase inhibitors in cardiovascular diseases. Issue 1 (January 2021) - Moretto, Johnny; Pudlo, Marc; Demougeot, Céline
Graphical abstract: Highlights: Arginase is a ubiquitous enzyme involved in nitric oxide- and polyamine-dependent vascular homeostasis. In vitro and ex vivo human data demonstrated that overactive arginase is a key event of endothelial dysfunction, a hallmark of cardiovascular diseases. Preliminary clinical studies confirmed that arginase inhibition is a promising therapeutic option for the treatment of cardiovascular diseases. Only a few available arginase inhibitors are suitable for clinical use, and more research is needed. Arginase is a ubiquitous enzyme that regulates polyamine- and nitric-oxide-requiring vascular functions. It is well-established that, in mammals, arginase overactivation contributes to endothelial dysfunction, a hallmark of cardiovascular diseases. The pharmacological potential of arginase inhibition for improving vascular function is largely supported by a wide range of data from animal studies. However, caution is required before extrapolating animal data to humans because interspecies differences in arginase expression and localization have been observed. For this reason, this review presents the existing arguments from human data in favor of a role of arginase in cardiovascular diseases. Then, the available data from clinical studies are discussed, as well as the possible arginase inhibitors that might be used in future large-scale clinical trials.